The Corporate Financial Policy and the Firm Value - Rana Shahid Imdad Akash; Majid Imdad Khan; Falik Shear (International Journal of Business and Economic Affairs, 2023)
The capital structure remained a hot debate from few decades. Capital structure in relation to firm’s value in developing economies was examined from January 1, 2013 to Dec 30, 2022. A lot of studies were conducted to get a better solution regarding a mix of results were drawn regarding capital structure to attain best mix of financing. The problem is the validity of the model is vague due to inappropriate estimation. The inappropriate estimation leads towards puzzling decisions. To avoid the puzzling decisions, the Extreme Bound Analysis (EBA) method is applied for examining the validity of the model. The results indicate that there is mix effect of capital structure on the value of the firm. The Return on Equity (ROE) has been negative and significantly affected whereas Operating Profit Margin (OPM) has been significant and positive affected. The other factors of value of the firm have negative relation with capital structure. The hypothesis four (04) explored the significant robust variables – Market Value Added (MVA), Return on Assets (ROA), Economic Value Added (EVA), ROE, Tobin’s Q (TQ), and Earning Per Share (EPS). The results for these variables remained persistent regarding policy making. The optimal capital structure accelerates value additive resources in firm value, and financial levels deviate in different regions requiring particular attention. The analysis could also be extended to financially constrained and unconstrained firms.